Research on the Design and Implementation of Music Teaching from the Perspective of Project-based Learning - Nan, Jiang (Journal of Educational Research and Policies, 2025)
In recent years, with the deepening of education reform, project-based learning, as a student-centered teaching model, has shown unique value in the field of music education. Based on the practical research of music teaching in kindergartens and primary and secondary schools, this paper explores the design and implementation strategies of project-based learning in music education. Research has found that project-based learning can effectively solve problems such as “lack of interest”, “ragmented experience” and “neglect of abilities” that exist in traditional music teaching. It can significantly improve students’ musical literacy and comprehensive abilities through the creation of real situations, interdisciplinary integration and diverse results. This article systematically explains the framework of project-based music teaching from the aspects of design concept, activity generation, implementation path, etc., and verifies its effectiveness with specific cases, providing theoretical reference and practical guidance for the innovation of music education.